PERAN ORANG TUA DAN KEPALA SEKOLAH DALAM PEMBINAAN AKHLAK SISWA DI MTS ZAHROTUL ISLAM TEGALREJO DRINGU PROBOLINGGO - Holilah, Nur; Muhammad, Devy Habibi; Adawiyah, Robiatul (LPPM STAI Muhammadiyah Probolinggo, 2024)
This research explores the role of parents and school principals in developing student morals at MTS Zahrotul Islam Tegalrejo Dringu Probolinggo. Using a descriptive qualitative approach, data was collected through interviews, observation and documentation at a school. Qualitative analysis was carried out to process field data with the steps of Data Collection, Data Reduction, Data Presentation, and Drawing Conclusions. The focus of the research is the validity of data regarding